2019
DOI: 10.1096/fj.201900522r
|View full text |Cite
|
Sign up to set email alerts
|

The topological key lncRNA H2k2 from the ceRNA network promotes mesangial cell proliferation in diabetic nephropathyviathe miR‐449a/b/Trim11/Mek signaling pathway

Abstract: Evidence has shown that long noncoding RNAs (IncRNAs) in the competing endogenous RNA (ceRNA) network are involved in various diseases. However, there is a lack of studies of the ceRNA network in diabetic nephropathy (DN). In this study, we investigated the effect of IncRNAs on mesangial cell (MC) proliferation in DN‐related ceRNA networks. Differences in IncRNA and mRNA expression between DN and normal mouse kidney tissues were detected with RNA‐seq, and DN‐related IncRNA/mRNA/microRNA (miRNA) ceRNA networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Many studies have reported that lncRNAs participate in DN through regulating target gene expression 20,21 . For example, silencing of the lncRNA XIST contributed to preventing renal interstitial fibrosis in DN 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that lncRNAs participate in DN through regulating target gene expression 20,21 . For example, silencing of the lncRNA XIST contributed to preventing renal interstitial fibrosis in DN 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNA (lncRNA) is one type of noncoding RNA, which is longer than 200nt and without coding potential. 4 LncRNA has been widely studied in various diseases, including diabetes, 5 cardiovascular disease 6 and bone disease. 7 LncRNA can be classified as intronic lncRNA, intergenic lncRNA, promoter associated lncRNA, antisense lncRNA, and untranslated region (UTR) associated lncRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Several ceRNAs have been shown to interact with TFs, miRNAs, or lncRNAs that result in altered gene expression during disease and cancer progression (Tay et al, 2014). In DN, several studies reported function of lncRNA as ceRNAs in affecting signaling pathways (Chen et al, 2019;Ji et al, 2019). In this study, we identified DEGs as ceRNAs that have negative coexpression with the shared miRNAs, let-7a-5p, miR-21, miR-30a, miR-29b, etc.…”
Section: Discussionmentioning
confidence: 87%